Wearable ultraviolet sensing fibers embedded with carbon nanotubes and zinc oxide nanowires. (1st December 2022) - Yang, Jonguk; Jeong, Sang-Mi; Seo, Keumyoung; Lim, Taekyung; Ju, Sanghyun
Abstract: Owing to the increasing interest in personal health, the real-time measurement of the exposure to ultraviolet (UV) rays during outdoor activities is a key technology that could be widely applied in the field of smart healthcare. Although wearable sensors that respond to UV intensity are being investigated, the development of sensors with stable durability and excellent sensing characteristics, despite movements, such as bending and exposure to external factors, including sweat and rain, is insufficient. In this study, we fabricated a wearable UV fiber sensor by embedding conductive carbon nanotubes (CNTs) and UV-sensitive zinc oxide nanowires (ZnO NWs) into highly elastic spandex fiber via a simple dipping-drying procedure. The ZnO NWs and CNTs coated in the form of a network inside the strands that constitute the spandex fiber enhanced the stability of the UV sensing measurements despite external changes, such as bending. In addition, by coating hydrophobic (3, 3, 4, 4, 5, 5, 6, 6, 7, 7, 8, 8, 9, 9, 10, 10, 10-heptadecafluorodecyl)phosphonic acid onto the ZnO NWs, the current distortion of the UV sensing channel due to contact with liquid could be prevented. It was confirmed that the fiber-based UV sensor, in which ZnO NWs and CNTs are networked, responds sensitively to UV in an environment with exposure to water or sweat.